PENGARUH LIKUIDITAS, SOLVABILITAS, ENVIRONMENT SOCIAL GOVERNANCE (ESG) DISCLOSURE TERHADAP KINERJA KEUANGAN - Muhammad Hafizd Fatahillah; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2025)
This study aims to examine the impact of financial ratios, such as liquidity, solvency, and Environment Social Governance (ESG) Disclosure, on financial performance. The financial ratio variables used in this study include Current Ratio (CR), Debt to Total Assets (DTA), and ESG Disclosure, while the dependent variable is Return on Assets (ROA). The sample for this study was determined using the purposive sampling method from companies listed on the Indonesia Stock Exchange (IDX), specifically those included in the LQ45 index from 2019 to 2023. A total of 225 samples were obtained. The analytical method employed is multiple linear regression analysis, conducted using IBM SPSS 30.The results of this study indicate that liquidity has a positive and significant effect on the company's financial performance, solvency has a positive but insignificant effect on the company's financial performance, and ESG Disclosure has a positive and significant effect on the company's financial performance. These findings indicate that the company's ability to meet short-term obligations and openness to environmental, social, and governance aspects are important factors in improving financial performance. Meanwhile, although solvency shows a positive direction of influence, its insignificance suggests the need for further evaluation regarding the management of the company's debt structure.